(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This article analyzes the soirées organized by the Ermelino Matarazzo Cultural Movement. The study addresses two productive fronts: a) the media transmissions of the soirées and b) the codes of an activist culture articulated in these meetings. Using the cartographic method, based on theories of difference, we trace the communicational landscape of the soirées and the collective as a space resulting from a cultural occupation. On another front, the Semiotics of Culture makes it possible to understand the soirées of the collective as a fabric of meanings, affections and heterogeneous processes, which are articulated in the face of social inequalities in the city of São Paulo.